Теоретичні основи матеріально-технічного забезпечення Збройних сил в українській військовій літературі 20–30-х років ХХ ст. - Мельник, Р. П. (Видавництво Львівської політехніки, 2014)
На підставі нових архівних документів розкрито проблему матеріально-технічного забезпечення Збройних сил в працях військовиків інтернованої армії Української Народної Республіки. Показано основні спроби військових інтернованої армії УНР спроектувати єдиний напрямок побудови регулярної армії національного зразка. Це питання тісно пов’язане із розробкою воєнної доктрини, яка в основі закладалась із положеннями матеріального і технічного забезпечення армії, у військовий і в мирний час. The thesis is devoted to complex research of Ukrainian military theoretical thought of the interwar period. Based on the deep analysis and systematization of a wade range of sources, it highlights the main stages of the conceptual approaches as to the principles of military engineering in the period of liberation competitions of 1917–1921 in the studies of military historians. It elucidates the role the Ukrainian military authors played in the exploration of the theoretical regulations of the military doctrine in the scientific papers as regards the national construction of the armed forces. The research examines the organization, areas and achievements of the scientific-historical and military-theoretical work of the military researchers of the diaspora. The author analyses historical experience of military engineering in the days of the national revolution 1917–1921 in scientific and memoirs-analytical works of military historians in the period of the Central Rada, Hetmanate, Directory and Western Ukrainian People’s Republic. It is emphasized that the dominant issue of the studies being analyzed and of the memoirs-analytical works of military historians was the history of the Ukrainian Revolution 1917–1921 and the analysis of the military engineering of that time. Deep comprehension and examination of the armed forces formation in the time of the liberation competitions allowed the military experts to start scientific theoretical work aimed at studying the military doctrine and therewith lay the foundation for building a regular military force with all its components.
Keywords: військовики; Українська Народна Республіка; архівні документи; матеріально-технічне забезпечення; воєнна доктрина; Ukrainian Republic of People's; military doctrine; the archived documents; logistical support; military theoretical